PERANCANGAN BUTTERFLY EDUPARK MELALUI METODE BIOMIMIKRI DI PALANGKA RAYA: Indonesia - Leilani, Jesica; F. Adji, fredyantoni; Dian Sanitha, Onie (JURNAL PERSPEKTIF ARSITEKTUR, 2025)
The lack of concern for the ecosystem and limited knowledge about butterflies, emphasizes the urgency to present a place that can display or demonstrate the life of butterflies as a means of education, recreation, and conservation in Palangka Raya. As a built open space that has ecological and social functions, harmony between the two is important to create an optimal area in terms of butterfly habitat conservation. By imitating the mechanism of life and how butterflies can adapt to the surrounding environment through the principle of biomimicry adaptation, it is expected to be able to provide a positive relationship between habitat, humans, and the surrounding environment. The idea applied comes from the life cycle of butterflies which is implemented through the form of organisms and the behavior of butterflies. Combining natural elements and creating an interactive and harmonious experience with the surrounding environment, Butterfly Edupark is here to increase knowledge, awareness, and pro-conservation attitudes to the Palangka Raya community through education.